2012
DOI: 10.1159/000342146
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Computed Analysis of Electroglottographic Signals in Muscle Tension Dysphonia

Abstract: Objective: To investigate the usefulness of electroglottography (EGG) parameters in the diagnosis and estimation of efficacy of voice therapy for muscle tension dysphonia (MTD). Patients and Methods: Nineteen MTD participants, an equivalent number of dysphonic (‘organic’) patients with vocal fold lesions and as many normal speakers were enrolled. Acoustic (Ac) and EGG signals during sustained phonation were recorded simultaneously. The period and amplitude perturbation quotient of both signals, the closed quot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 48 publications
3
15
0
Order By: Relevance
“…6, 2014 patients. 5 However, in this previous study, because we did not compare therapeutic and nontherapeutic groups, the therapeutic effects may have been a consequence of vocal hygiene or a natural (spontaneous) cure. Accordingly, in the present study, we investigated the immediate effects of humming on the EGG perturbation parameters to confirm the cause-result relationship between the performance of humming and decreased EGG parameters.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…6, 2014 patients. 5 However, in this previous study, because we did not compare therapeutic and nontherapeutic groups, the therapeutic effects may have been a consequence of vocal hygiene or a natural (spontaneous) cure. Accordingly, in the present study, we investigated the immediate effects of humming on the EGG perturbation parameters to confirm the cause-result relationship between the performance of humming and decreased EGG parameters.…”
Section: Discussionmentioning
confidence: 90%
“…We previously reported that MTD patients exhibit improved perceptual vocal quality and a reduced degree of supraglottic compression as well as decreased perturbation parameters of both acoustic (Ac) and electroglottographic (EGG) signals and the standard deviation of the contact quotient (CQ) following voice therapy primarily using humming. 4,5 However, because we did not compare therapeutic and nontherapeutic groups, it remains to be confirmed whether these post-therapeutic changes are actually conferred by the humming itself.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…20 Regarding voice therapy, EGG may as well be a very sensitive indicator of therapy progress. 21 Although literature shows the importance of EGG in voice evaluation, it lacks information about reliability of perturbation measurements derived from an EGG signal.…”
Section: E12mentioning
confidence: 99%